INNOVATION IN THE UTILIZATION OF VILLAGE RESOURCES FOR ECONOMIC EMPOWERMENT OF SUMBEREJO COMMUNITY - R., Alvi Alifia; Mu’tafi, Ali; L., Irma Aslikhatul; Nurhidayah, Julia; Q., Helen Zulfatul; A., M. Faza (LPPM Univ. Ibn Khaldun Bogor, 2025)
The Community Service Program (KKN) in Sumberejo Village, Wonosobo, emphasized the great potential of coconut fiber, which has long been underutilized. Although the village is known as a center for coconut sugar production, the leftover fiber is often simply piled up or burned, leading to environmental problems. Through this observation, efforts were made to transform coconut fiber into cocopeat, an environmentally friendly growing medium. The research process included a comparative analysis of planting media, interviews, field observations, and workshops. The findings showed that the community responded positively to the production of cocopeat. According to trials conducted on mustard greens and cucumbers, cocopeat was found to support better plant growth than pure soil. This improvement is supported by cocopeat’s strong capacity for water retention, its ability to ensure efficient air circulation, and its balanced nutrient composition. Along with enhancing agricultural productivity, this innovation also opens avenues for new community-driven enterprises. Therefore, converting coconut fiber into cocopeat not only contributes to addressing environmental challenges but also plays a vital role in building a stronger and more sustainable village economy.